Early steps of oxidative damage in DNA quadruplexes are position-dependent: Quantum mechanical and molecular dynamics analysis of human telomeric sequence containing ionized guanine - Asha, Haritha; Stadlbauer, Petr; Martínez-Fernández, Lara; Banáš, Pavel; Šponer, Jiří; Improta, Roberto; Esposito, Luciana (International journal of biological macromolecules, 2022)
Guanine radical cation (G•+) is a key intermediate in many oxidative processes occurring in nucleic acids. Here, by combining mixed Quantum Mechanical/Molecular Mechanics calculations and Molecular Dynamics (MD) simulations, we study how the structural behaviour of a tract GGG(TTAGGG)3 (hereafter Tel21) of the human telomeric sequence, folded in an antiparallel quadruple helix, changes when one of the G bases is ionized to G•+ (Tel21+). Once assessed that the electron-hole is localized on a single G, we perform MD simulations of twelve Tel21+ systems, differing in the position of G•+ in the sequence. When G•+ is located in the tetrad adjacent to the diagonal loop, we observe substantial structural rearrangements, which can decrease the electrostatic repulsion with the inner Na+ ions and increase the solvent exposed surface of G•+. Analysis of solvation patterns of G•+ provides new insights on the main reactions of G•+, i.e. the deprotonation at two different sites and hydration at the C8 atom, the first steps of the processes producing 8oxo-Guanine. We suggest the main structural determinants of the relative reactivity of each position and our conclusions, consistent with the available experimental trends, can help rationalizing the reactivity of other G-quadruplex topologies.
Keywords: Nucleic Acid Conformation; lidé; kvantová teorie; G-kvadruplexy; simulace molekulární dynamiky; Oxidative Stress; guanin; DNA; G-Quadruplexes; telomery; Humans; Guanine; ionty; Solubility; rozpustnost; konformace nukleové kyseliny; Quantum Theory; oxidační stres; Ions; Telomere; molekulární modely; Molecular Dynamics Simulation; Models, Molecular